Generative Learning Model to Improve Science Literacy Competence on 10th Grade Students of Sciences Wahid Hasyim Senior High School on Temperature and Heat Topic - Azizatuzzahro’, Azizatuzzahro’; Kartika, Ika (Proceeding International Conference on Science and Engineering, 2017)
This research was aimed to determine the effect of generative learning models on the competence of science literacy and to know the difference in the side of improvement of students' science literacy competence compared with control class on temperature and heat focus lesson. This educational research was a quasi-experiment research with Nonequivalent control group design. The independent variable of this research was generative learning model and the dependent variable was students’ science literacy competence. This research was conducted in of one school in Sleman through saturated sampling technique. The experiment class is 10th grade students of 1st class and the control class is 10th grade students of second class. We used pretest and posttest as data collection instruments. The data analysis used descriptive statistic with measure of central tendency and size of dispersion include Normalized Gain and effect size. The result of this research showed that there was an effect of generative learning model in case of students’ science literacy competence on temperature and heat focus lesson with average 38,00 for pretest and 79,20 for posttest. There was also improvement on students’ science literacy competence with moderate improvement category, which was indicated by N-Gain value of experimental class 0.66. The control class which was treated with direct instruction model was also increased with N-Gain value of 0.48 or included in the moderate category also. The improvement of the experimental class has a very significant difference with the control class indicated by the effect size value of 1.028.